Prevalence of goiter and thyroid nodules before and after implementation of the universal salt iodization program in mainland China from 1985 to 2014: a systematic review and meta-analysis. - Wei Zhao; Cheng Han; Xiaoguang Shi; Chuhui Xiong; Jie Sun; Zhongyan Shan; Weiping Teng (PLoS ONE, 2014)
Objectives We comprehensively estimated the prevalence of goiter and thyroid nodules (TNs) before and after the implementation of the Universal Salt Iodization (USI) program in mainland China and provided information for creating effective health policies. Methods PubMed, Google Scholar, CNKI, Chinese Wanfang and Chongqing VIP databases were searched for relevant studies from Jan 1985 to Feb 2014. Data from eligible citations were extracted by two independent reviewers. All analyses were performed with Stata 11.0 and SPSS 17.0. Results Eligible articles (N = 31; 4 in English and 27 in Chinese) included 52 studies (15 about goiter rates made before 1996 and 14 afterwards, and 23 about TNs). Our meta-analysis suggests a pooled prevalence for goiter before and after 1996 and for TNs of 22.8% (95% CI: 15.3%, 30.3%), 12.6% (95% CI: 9.4%, 15.8%) and 22.7% (95% CI: 18.3%, 27.0%), respectively. Egger's test of three independent categories revealed no evidence of publication bias (p = 0.101, 0.148 and 0.113, respectively). Conclusions The prevalence of goiter was reduced by almost half after 1996 in mainland China, so the USI program was considered beneficial. However, subgroup analysis suggests that both insufficient and excess iodine may be associated with goiter. The prevalence of goiter and TNs increased significantly after 2002, suggesting a risk of excessive iodine intake. Thus, salt iodization standardizations should be set according to local conditions.